Pengaruh Bauran Pemasaran Terhadap Minat Beli Ulang Konsumen Gerai Es Teh Indonesia Di Kota Serang - Nurlia Putri, Nezly; Alkhaliq, Barkah; Cendana Kusuma, Aria (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2022)
The market demand for ready-to-drink beverages has increased significantly. This can be seen from the many drink outlets of various brands and types of contemporary drinks that continue to appear in the midst of Indonesian society. This study aims to determine the effect of the marketing mix on consumer repurchase intention and the most influential factors on consumer repurchase interest of Es Teh Indonesia Outlet consumers in Serang City. The variables used in this study are product, price, place, promotion, people, physical facilities and processes. All of these variables are independent variables, while as the dependent variable is the buying interest. Data collection techniques were carried out by distributing online questionnaires and had been filled out by 100 respondents. The number of respondents used was 30 respondents with the criteria of having bought and consumed Es Teh Indonesia drinks. The sampling technique used is non-probability sampling, and the sampling method used is judgmental sampling. The method used in this research is descriptive statistical analysis. The results showed that all marketing mix variables simultaneously have no significant effect on repurchase intention of Indonesian Ice Tea drinks with a significance level of 0.066 which is greater than 0.05 level of significance. Meanwhile, the marketing mix variable that has the most influence on consumers' repurchase interest at Es Teh Indonesia Outlet in Serang is the type of product offered, with a value of  = -0.176.